2023
DOI: 10.1002/fft2.217
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of water bamboo shoot (Zizania latifolia) extracts against acute alcoholic liver injury in a mice model and screening of bioactive phytochemicals

Abstract: In this study, the hepatoprotective effect of alkali extract (NE) of water bamboo shoot (WBS) against acute alcoholic liver injury (ALI) in mice was evaluated, and its underlying mechanisms were explored. Animal experiment demonstrated that NE exhibited hepatoprotective effect on alcoholic intake‐induced ALI via significantly enhancing the hepatic activities of alcohol dehydrogenase (ADH), acetaldehyde dehydrogenase (ALDH), superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px), and catalase (CAT), wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…These results indicated that different types of inulin and HDT water extract could activate the activities of ADH and ALDH to a certain extent, promote the metabolism of ethanol and acetaldehyde, and alleviate the injury caused by acute alcohol poisoning. This is consistent with the results of previous studies (Gao et al, 2023; Yang et al, 2023)…”
Section: Resultssupporting
confidence: 94%
“…These results indicated that different types of inulin and HDT water extract could activate the activities of ADH and ALDH to a certain extent, promote the metabolism of ethanol and acetaldehyde, and alleviate the injury caused by acute alcohol poisoning. This is consistent with the results of previous studies (Gao et al, 2023; Yang et al, 2023)…”
Section: Resultssupporting
confidence: 94%